Difficulties of Accrual Accounting Implementation in Indonesian Government: a Comparative Study - Pratama, Arie (Jurnal Akuntansi Multiparadigma, 2012)
Abstract: Difficulties of Accrual Accounting Implementation in Indonesian Government: a Comparative Study. The research aims to compare the condition in Indonesia and other country that apply accrual accounting. The research method employed is qualitative descriptive. Data collected by the literary study, and interview. The research was conducted from November 2008 until January 2009. Analysis methods used were qualitative for data that was collected using literary study as well as content analysis for data that was collected using interview. The conclusions of this research are: the Human Resources Competencies, Public Finance Practice, and Regulation are factors that determined diffi culties in the implementation of accrual accounting in Indonesia and also in other country which implement the accrual accounting Abstrak: Kesulitan Implementasi Akuntansi Akrual di Pemerintahan Indonesia: Suatu Studi Komparatif. Riset ini bertujuan mengkomparasi kondisi di Indonesia dan negara lain yang mengaplikasikan akuntansi akrual. Metode riset yang digunakan adalah deskriptif kualitatif. Data dikoleksi melalui studi literatur dan wawancara. Riset dilakukan sejak November 2008 hingga Januari 2009. Metode analisis yang digunakan adalah dengan pendekatan kualitatif untuk data yang dikoleksi melalui studi literatur dan metode analisis konten untuk data yang dikoleksi dengan wawancara. Simpulan riset ini menunjukkan bahwa kompetensi sumber daya manusiam praktik keuangan publik dan peraturan merpakan factor yang menentukan kesulitan implementasi akuntansi akrual di Indonesia dan di negara yang lain yag juga mengaplikasikan akuntansi akrual.